Transethosome-mediated curcumin delivery promotes superior wound healing with reduced toxicity - Meriem Rezigue; Alaa A. A. Aljabali; Walhan Alshaer (Pharmacia)
Background: Curcumin is a natural compound with anti-inflammatory, antimicrobial, and antioxidant effects; however, its clinical use in wound care is restricted by its poor water solubility and low skin absorption. Chronic wounds, often associated with infection and delayed healing, necessitate targeted and effective treatment strategies. Methods: Transethosomes were developed to improve the topical delivery of curcumin. Their size, structure, and stability were assessed using standard techniques, including dynamic light scattering and electron microscopy. Drug distribution in skin layers was measured through ex vivo studies, and FTIR analysis was used to evaluate barrier disruption. Antibacterial activity and cytotoxicity were evaluated in vitro, and wound healing was assessed using an in vitro scratch assay. Results: The optimized formulation had a size of 115.8 ± 4.9 nm, low polydispersity index (0.127 ± 0.022), and nearly complete drug loading (99.7%). Skin deposition of curcumin was significantly higher than that in the control (p < 0.05) across all layers, with minimal systemic absorption. FTIR confirmed lipid disruption in the stratum corneum. Antimicrobial testing showed preserved activity against Staphylococcus aureus. Importantly, the formulation was less toxic to healthy cells (IC₅₀: 12.76 µg/mL vs. 6.2 µg/mL for the free drug). Wound healing assays showed 25% faster closure, reaching full repair in 72 hours. These biological endpoints confirmed that enhanced skin deposition was accompanied by improved therapeutic performance. Conclusion: Transethosomes improved curcumin skin delivery, reduced its cytotoxicity, and accelerated wound healing in vitro. This formulation offers a promising strategy for skin-targeted drug delivery, especially in chronic wound care, and supports further testing in advanced wound models in the future.